THE EFFECT OF INTELLECTUAL CAPITAL ON HEPTAHELIX MANAGERIAL PERFORMANCE AND ITS IMPLICATIONS FOR COMPETITIVE ADVANTAGE: A TNI AL SURVEY IN RIAU ISLANDS - Sidabutar I.M.S.; Fadli M.; Nuh M.; Widagdo S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
The objective of this research was to examine the effect of Intellectual Capital on Heptahelix Managerial Performance, the effect of Heptahelix Managerial Performance on Competitive Advantage, the effect of Intellectual Capital on Competitive Advantage, and the effect of Intellectual Capital on Competitive Advantage through Heptahelix Managerial Performance. The novelty of this research is that this research investigates the level of personal performance by combining the concept of Pentahelix and Technology and the concept of measuring Managerial Performance in the Indonesian Navy (TNI AL), Riau Islands Province, or what is referred to as Heptahelix Managerial Performance. It is expected that this research can create superior human resources in the Indonesian Navy in Riau Islands Province so that they can deal with illegal actions which are the main tasks and functions of the Navy to maintain defense and security in the Marine Territory of the Republic of Indonesia, especially in the Riau Islands Province. This research employed the associative method to see the relationship of effects and is explanatory from the existing theory by using the Structural Equation Modeling (SEM) method with LISREL Software.